Answer: (2,-3)
Explanation:
To solve by elimination method, we need to choose which variable to eliminate. Let's eliminate y. We need to make sure that the y coefficients in both equations are equal. To do that, you multiply the first equation by 5 and the second by 9.
(11x + 9y = -5)5 [multiply entire equation by 5]
(7x + 5y = -1)9 [multiply entire equation by 9]
--------------------------------------------------------------------------------------------------------
55x+45y=-25
63x+45y=-9
Now that the y are both the same, we can eliminate y by subtracting both equations and solve.
-8x=-16 [divide both sides by -8]
x=2
Now that we have x=2, we can plug that in to any equation to find y.
7(2)+5y=-1 [multiply]
14+5y=-1 [subtract both sides by 14]
5y=-15 [divide both sides by 5]
y=-3
With the y-value, we know that the answer is (2,-3).